Between capitals, habitus and socio-institutional conditions: the positions and position-taking of teachers-researchers at the National University of San Juan (Papeles, 2024)
The purpose of this article is to investigate the recent configuration of the so-called academic profesión at the National University of San Juan (UNSJ). For that, two analytical dimensions are addressed: the positions of the teaching staff in the academic structure (according to their positions, categories and dedications) and their heterogeneous position-takings based on their held capitals and differential profiles of production and circulation of knowledge. The proposal is derived from a line of research developed at the Institute of Socioeconomic Research (IISE, Faculty of Social Sciences) of the UNSJ, within the framework of the CICITCA-UNSJ Project called Cartography of the academic profession at the National University of San Juan (2019-2024), accredited by the No. 0116-FCS-UNSJ-2023 Resolution. The paper has been approached from a relational methodological approach, articulating a statistical-documentary Access aimed at recreating the configuration objective conditions of the academic space studied, with an ethnographic Access focused on recovering the teaching and research experiences of teachers at the University, based on their own testimonies.
Keywords: teaching trajectories; academic structure; scientific capital; positions; taking positions